INFLUENCE OF CHILD ABUSE AND NEGLECT ON THE EMOTIONAL WELL BEING OF STUDENTS OF FEDERAL POLYTECHNIC OROGUN, DELTA STATE - Okevwo, Precious; Arienmughare , Emmanuel (The Indonesian Journal of Social Studies, 2025)
The study investigated the influence of child abuse and neglect on the emotional well-being of students of Federal Polytechnic Orogun. The study adopted an Expo-factor research design. The population of this study comprised 136 undergraduate students of Federal Polytechnic Orogun, Delta State. A census sampling technique was used to select undergraduate students. Instrument title: “Influence of Child Abuse and Neglect on the Emotional Well-Being of Students Questionnaire (ICANEWBSQ)” was used for data collection. The findings revealed that respondents are of the opinion that prevalent types of child abuse and neglect experienced by students include physical abuse, emotional abuse, sexual abuse, parental neglect and verbal abuse and also, respondents are of opinion that how child abuse and neglect impact the mental health outcomes of students at Federal Polytechnic Orogun The study recommended among others that administration at Federal Polytechnic Orogun should be proactive in implementing mandatory training for faculty, staff, and students to recognize the signs of child abuse and neglect and also to build awareness and equip the campus community with the knowledge to identify and report abuse.